TRADISI ADAT JAWA DALAM MENYAMBUT KELAHIRAN BAYI (Studi Tentang Pelaksanaan Tradisi Jagongan Pada Sepasaran Bayi) di Desa Harapan Harapan Jaya Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Widyaningrum, Listyani; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Harapan Jaya Village, Pangkalan Kuras Sub-district, Pelalawan Regency. With the formulation of the problem (1) How the system of implementation of jagongan tradition on baby’ Sepasaran at Harapan Jaya Village Pangkalan Kuras subdistrict Pelalawan regency. The purpose of this research is to know the system of jagongan tradition in baby’s sepasaran for Javanese people in Harapan Jaya Village Pangkalan Kuras Subdistrict of Pelalawan Regency, to rules procedure jagongan tradition on baby’s sepasaran for Javanese people in Harapan Jaya Village Pangkalan Kuras Sub-district, Pelalawan Regency to know the difference execution of jagongan tradition at baby’s sepasaran for Java society in Harapan Jaya Village Pangkalan Kuras Sub-district of Pelalawan Regency. This research is a descriptive qualitative research with the research subjects selected by purposive sampling that the selection of informants in this study determined deliberately. With the number of informants as many as 8 respondents, the data collection taken from the primary data is the direct data concerning the opinion of the informant about the research variables obtained from the answers of interviews and secondary data is data obtained to complete the data. With data collection techniques such as observation (observation), interviews, and documentation. So get respondents 1 person key informant, 5 respondents, and 2 respondents as local community. Based on the results of the research can be concluded that the tradition of baby jagongan is very suitable and become its own characteristic of rural Javanese society that prioritizes the sense of kinship and empathy. Baby jagongan tradition is only done when there is a baby only and carried out from the birth of the baby up to seven hari.tradisi baby jagongan filled with playing cards playing cards, dominoes, chess, and other games. Benefit from the implementation of baby jagongan that can be gathered with relatives, supplies of equipment and baby supplies helped, relationships among other villagers more closely, the atmosphere of the house to be crowded, and the mother who had just given birth feel comforted and someone to accompany. One of the intentions of this jagongan is as a congratulation to families who have a celebration without giving something memorable like money and goods. Keywords: Java Community, Jagongan Tradition, Baby’s Sepasaran.